The Human Factor of Cybercrime (Taylor & Francis, 2019)
Cybercrimes are often viewed as technical offenses that require technical solutions, such as antivirus programs or automated intrusion detection tools. However, these crimes are committed by individuals or networks of people which prey upon human victims and are detected and prosecuted by criminal justice personnel. As a result, human decision-making plays a substantial role in the course of an offence, the justice response, and policymakers' attempts to legislate against these crimes. This book focuses on the human factor in cybercrime: its offenders, victims, and parties involved in tackling cybercrime. The distinct nature of cybercrime has consequences for the entire spectrum of crime and raises myriad questions about the nature of offending and victimization. For example, are cybercriminals the same as traditional offenders, or are there new offender types with distinct characteristics and motives? What foreground and situational characteristics influence the decision-making process of offenders? Which personal and situational characteristics provide an increased or decreased risk of cybercrime victimization? This book brings together leading criminologists from around the world to consider these questions and examine all facets of victimization, offending, offender networks, and policy responses.
English
Keywords: cybercrime; human factor; thema EDItEUR::J Society and Social Sciences::JK Social services and welfare, criminology::JKV Crime and criminology; thema EDItEUR::U Computing and Information Technology::UB Information technology: general topics::UBJ Digital and information technologies: social and ethical aspects; thema EDItEUR::U Computing and Information Technology::UY Computer science::UYZ Human-computer interaction